Pelaksanaan Pembelajaran Seni Budaya Kelas XII MIPA 2 SMA Negeri 1 Kota Sawahlunto - Wedi Juanda; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2019)
This article aims to describe the implementation of learning art and culture (contemporary music) class XII of MIPA 2 SMA Negeri 1 Sawahlunto. This type of research is qualitative research using descriptive method. The main instrument in this study is the researchers themselves and assisted with assisted with observation, interviews, and documentation and study of the literature. The technique of data collection is done by way of observation, interview, documentation and study of the literature. Techniques in analyzing the data is carried out by means of the data processing directly after the field. The results showed that teachers design a simpler contemporary music learning to teach in order to be digested by students given that the study of contemporary music is not a little. In the performance of contemporary music learning, learning that implemented teacher different to what has been written into the draft implementation of learning (RPP). Still found some weaknesses against the methods and strategies that teachers use against learning. Teachers should increase the motivation of students to more focused in the art and cultural learning by doing approach individuals and groups. Facilities and infrastructure provided the school is still minimal, resulting in learning not to be implemented properly.